The impact of regional diversification in the size of the general government sector on the economies of EU countries - Mroczek, Teresa; Skica, Tomasz; Rodzinka, Jacek (Wpływ regionalnego zróżnicowania rozmiaru sektora finansów publicznych na gospodarki państw Unii Europejskiej, 2019)
The main objective of this article is proving how the regional diversification in the size of general government sector influences the economies of EU countries. To achieve this, presenting both the size of the general government sector and of the economy, using variables which enable comparison in time and space, is essential. Bearing this in mind, the general government sector has been depicted by nine variables and the economy has been described by thirteen explanatory variables. The complexity of the phenomenon imposes the implementation of an unconventional approach in this field of exploration. Our approach is based on Intelligent Data Analysis (IDA) - a methodology that includes a set of techniques that can be applied for extracting useful knowledge from large amounts of data. In order to indicate the impact of regional diversification in the size of the general government sector on the EU countries’ economies, probabilistic techniques were applied – Bayesian Networks. Analysis made in the study showed that the largest impact of the GGS size on the economy was identified in Portugal and Slovakia. The results of the studies show that the most "responsive" to the size of the GGS variable describing the economy was gross domestic product per inhabitant. The research proved that the economies of some countries showed similarities in the effect of the size of the general government sector on the parameters of the economy. We have identified five groups of such countries
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 65-80
Keywords: general government sector size; economy; public finance; impact of size of the general government sector on the economy; Bayesian networks; probabilistic inference; wielkość sektora instytucji rządowych i samorządowych; gospodarka; finanse publiczne; wpływ sektora instytucji rządowych i samorządowych na gospodarkę; sieci Bayesa; wnioskowanie probabilistyczne